Investigating the Deep Learning Approach and Lampung Cultural Values (Piil Pesenggiri): A Theoretical and Cultural Analysis - Prastyo, Yanuar Dwi; Ariyani, Farida; Ubaidillah, Muhammad; Zakiya, Hanifah; Rahayu, Chika; Dharmawan, Yanuarius Yanu (Linguistics and ELT Journal, 2025)
This conceptual paper investigates how the deep learning approach articulated in the New Pedagogies for Deep Learning (NPDL) framework can be theoretically and culturally aligned with Indonesian national graduate profiles, recent Indonesian government formulations of Pembelajaran Mendalam (PM), and the Lampung cultural philosophy of Piil Pesenggiri in the context of English language teaching (ELT). Drawing on document analysis of NPDL texts, Indonesian curriculum and policy documents, the Academic Paper on Deep Learning, scholarly discussions of graduate profiles, and regional literature on Piil Pesenggiri, the study develops a tri-level comparison between global, national, and local frameworks. The analysis shows that NPDL’s six global competencies-character, citizenship, collaboration, communication, creativity, and critical thinking-broadly converge with Kemendikdasmen’s holistic, competency-based vision of graduates and with national deep learning discourse, which combines knowledge, skills, character, and citizenship in integrated graduate profiles. At the local level, core elements of Piil Pesenggiri such as juluk adok, nemui nyimah, nengah nyappur, and sakai sambayan provide cultural resources that can support the social, ethical, and collaborative dimensions of deep learning, while also generating tensions around honour, face, hierarchy, and group harmony. The paper argues that, when these convergences and tensions are explicitly recognised, ELT classrooms in Lampung can be designed as spaces for deep learning projects that develop the 6Cs through locally meaningful themes, tasks, and interaction norms. The study concludes by outlining principles for culturally responsive, deep learning-oriented ELT and by suggesting directions for future empirical research on the localisation of global pedagogies and national deep learning reforms in Indonesian schools.